The effect of acupuncture on stroke recovery: study protocol for a randomized controlled trial - Liu Huilin; Zhang Dangsheng; Tan Xiuge; Yang Daqing; Wang Guiling; Zhao Yin; Wen Yali; Shi Guangxia; Wang Linpeng (BMC, 2012)
Abstract Background Stroke is one of the leading causes of death and disability in China. Current treatments for stroke are limited and achieve no optimal effect. Acupuncture is widely used in the treatment of stroke and in improving the quality of life for patients in China. In most previous clinical studies, the effects of acupuncture have been diverse, and few well-designed randomized controlled trials have been conducted to investigate the long-term effect of acupuncture on acute stroke recovery. Method Three hundred and twenty eight subjects with acute cerebral apoplexy will be recruited. The patients will be randomized into two different groups: the intervention group will receive acupuncture treatment together with Western standard treatment for 2 weeks plus the secondary prevention treatment for 22 weeks; the control group will receive only the Western standard treatment for 2 weeks and the secondary prevention treatment for 22 weeks. The primary outcome measures are Barthel Index and the Stroke-Specific Quality Of Life. The secondary outcome measures are the National Institutes of Health Stroke Scale and Modified Rankin Scale. All assessments will be conducted at the baseline and at weeks 4, 12 and 24 of follow-up. Discussion This study will evaluate the effects of acupuncture on the long-term recovery of acute stroke and on improving the quality of life of the patients. The results of this study will help establish optimal integrated therapeutic strategies for patients with stroke. Trial registration Current Controlled Trials ISRCTN29932220